UNDERSTANDING EMPLOYEES’ READINESS FOR CHANGE IN SMALL AND MEDIUM-SIZED ENTERPRISES: A MULTIDIMENSIONAL COMMUNICATION FRAMEWORK (The South East European Journal of Economics and Business, 2026)
Drawing on internal communication and organizational change literature, this study develops a conceptual framework that examines the influence of internal communication on employee readiness for change. In theory, internal communication is recognized as an important prerequisite for employees’ perceptions and acceptance of change. Nevertheless, its role in small and medium-sized enterprises (SMEs) is not sufficiently studied, especially in the post-COVID-19 context which altered many communication preferences. To fill this gap, the proposed framework combines Internal Communication Satisfaction and perceived Quality of Change Communication, together with Work Demands and Information Overload as workplace stressors. The hypotheses were empirically tested through a quantitative survey of 454 employees from Croatian SMEs. Using a disjoint two-stage PLS-SEM approach, the findings confirmed that both Internal Communication Satisfaction and perceived Quality of Change Communication positively affect employee Readiness for Change. Results additionally revealed moderating and complementary mediating effects. The study has several theoretical contributions and offers practical implications for management.